Plasma CPU-86017 concentrations regarding suppression of ouabain-induced cardiac arrhythmias and decrease of heart rate in guinea pigs - Khan Hussien Hamed; Dai De-Zai; Xiao Da-Wei; Lin Sheng; Wang Zi-Zheng; Lou Sheng; Qing Qing (Acta Pharmacologica Sinica, 2016)
"AIM: To determine the effective plasma levels of CPU-86017 which could suppress the cardiac arrhythmias induced by i.v. ouabain in guinea pigs. METHODS: The cardiac arrhythmias and the heart rate were monitored by ECG traces. Blood samples were collected to determine plasma levels using HPLC assay. TXB2 and 6-keto-PGF1 alpha were measured in plasma. RESULTS: The plasma concentrations of CPU-86017 which were effective to suppress ventricular fibrillation (VF) and heart rate were 0.13-0.23 mg/L and 0.13-0.31 mg/L, respectively. A reduction of TXB2 levels and an elevation of 6-keto-PGF1 alpha levels were observed after CPU-86017 i.v. administration. CONCLUSION: The arrhythmia-suppressing and heart rate-slowing effect of CPU-86017 followed a linear relationship with its concentrations in plasma."